Analysis on ignition characteristics and stability of large length-diameter tube with high-low pressure chamber: Experimental and two-phase flow method research - Shenshen Cheng; Ruyi Tao; Xinggan Lu; Xiaoting Cui; Shao Xue (Case Studies in Thermal Engineering)
The large length-diameter ratio low-pressure tube, characterized by its long ignition channel and multiple ignition orifices distributed along its length, demonstrates an excellent ignition performance, emerges as an ideal ignition component for large-caliber combustion systems. However, due to the restriction of the ignition process within the tube by the initial ignition source, the high-low pressure chamber structure is commonly adopted to ensure the ignition performance. In order to effectively control the influence of the ignition source on the ignition performance of a long tube, this study conducted experiments and two-phase flow numerical simulations to analyze the diffusion and distribution characteristics of the gas and solid within the tube, exploring their propagation characteristics and stability. Multiple sets of repeated experimental results demonstrate the strong ignition stability of the high-low pressure ignition structure, with the consistent peak pressure and ignition time, where the time deviation is less than 0.04 ms and the pressure deviation is less than 0.17Mpa. Further, on the basis of experiment verification, the numerical calculation reveal that the flow field distribution within the tube is primarily influenced by the pressure variations in the high-pressure chamber, and membrane rupture pressure and charging density significantly affect the flow field distribution inside the chamber. Combined with the multi-parameter correlation analysis and assessment of impact degree, the adjustable or controllable parameters can be identified to achieve the objective of the system optimization. A higher membrane rupture pressure can effectively increase the pressure within the tube, reduce ignition time, and result in a larger area of solid dispersion. Although an increase in the charging density has a less pronounced effect on the pressure reduction and ignition time, it can enhance the concentration of solid particles within the tube.